Dampak Kawasan Industri Terhadap Persebaran Penduduk Di Cilegon - Silvia Ramdhani; Alya Zalfa Zahida (Jurnal Masyarakat Madani Indonesia, 2025)
This study analyzes the impact of industrial areas on population distribution in Cilegon, the largest industrial city in Banten Province. Using a mixed methods approach, this study examines post-industrialization demographic transformations through primary data (observations, questionnaires) and secondary data (BPS, government reports). The findings reveal that industrialization has triggered massive migration from rural to urban areas, with population density in industrial zones reaching 4,500 people per square kilometer (vs. 800 people per square kilometer in non-industrial areas), driven by pull factors such as employment opportunities (β=0.71) and higher wages (3.2 times rural income). Positive impacts include labor absorption (58% of the labor force), increased HDI (from 70.1 to 74.3), and SME development (12% annual growth). However, industrialization also causes spatial inequality (72% of the population concentrated in the north), infrastructure pressure (135% overcapacity), environmental degradation (ISPA +25%), and social conflicts (40% of cases). These findings confirm the core-periphery theory and urban overload. The study recommends industrial decentralization policies, strengthening urban-rural linkages, and improving sustainable spatial planning.